Divergent Functional Properties of the Ribosome-Associated Molecular Chaperone Ssb Compared with Other Hsp70s - Pfund, Christine (The American Society for Cell Biology, 2001)
Ssbs of Saccharomyces cerevisiae are ribosome-associated molecular chaperones, which can be cross-linked to nascent polypeptide chains. Because Ssbs are members of a divergent subclass of Hsp70s found thus far only in fungi, we asked if the structural requirements for in vivo function were similar to those of “classic” Hsp70s. An intact peptide-binding domain is essential and an alteration of a conserved residue in the peptide-binding cleft (V442) affects function. However, Ssb tolerates a number of alterations in the peptide-binding cleft, revealing a high degree of flexibility in its functional requirements. Because binding of Ssb to peptide substrates in vitro was undetectable, we assessed the importance of substrate binding using the chimera BAB, in which the peptide binding domain of Ssb is exchanged for the analogous domain of the more “classical” Hsp70, Ssa. BAB, which binds peptide substrates in vitro, can substitute for Ssb in vivo. Alteration of a residue in the peptide-binding cleft of BAB creates a protein with a reduced affinity for peptide and altered ribosome binding that is unable to substitute for Ssb in vivo. These results indicate that Ssb's ability to bind unfolded polypeptides is likely critical for its function. This binding accounts, in part, for its stable interaction with translating ribosomes, even although it has a low affinity for peptides that detectably bind to other Hsp70s in vitro. These unusual properties may allow Ssb to function efficiently as a chaperone for ribosome-bound nascent chains.